NGHIÊN CỨU THÀNH PHẦN HÓA HỌC LÁ CÂY SƠN TRÀ POILANE (ERIOBOTRYA POILANEI J.E. VID.), HỌ HOA HỒNG (ROSACEAE) I. TRITECPEN KHUNG URSAN - Thiện, Đinh Gia; Chiến, Trần Văn; Hoàng Anh, Nguyễn Thị; Sung, Trần Văn (Vietnam Journal of Chemistry, 2012)
Three triterpenes with the ursane skeleton were isolated from the n-hexane and ethyl acetate extracts of Eriobotrya poilanei's leaves collected in national park Bi Dup, Nui Ba, Lam Dong province. Their structures were elucidated by analysis of MS, NMR spectra and comparison with the published data. They are ursolic acid, ursolic aldehyd and  pomolic acid.